Tracer Study Alumni: Upaya Pengembangan Prodi Bimbingan Konseling Universitas Negeri Makassar - Bakhtiar, Muhammad Ilham; Latif, Suciani (Jurnal Kajian Bimbingan dan Konseling, 2017)
The aim of research to determine: (1) the profile of alumni student guidance and counseling; (2) a waiting period of alumni guidance and counseling; (3) the relevance of courses to the needs of the labor market; (4) the alumni users. This study is a qualitative research using descriptive survey method. The analysis conducted by the percentage and using three stages of data reduction, data presentation and conclusions. The results of this study through the instrument tracer study provides an overview achievement graduate GPA average of 78% or between 2.75 to 3.50 and there are 22% or 3.50 to 4.00 cum laude. The study period of Prodi Guidance and Counseling alumni is fairly fast 3.5-year study period, there were 13% and 68% of alumni completed the study precisely in the time period in 4 years. Similarly, waiting period to get their first job is very quick, the longest is 5 months with a percentage of 88%. The job mostly occupied by the alumni is as a Guidance and Counseling Teacher (66%). Users suggest competence enhancement of graduates in the field of foreign languages, especially English, skills or personal development skills, and mastery of technology needs to be developed.